[3+2] Cycloaddition of N-Aminopyridines and Perfluoroalkynylphosphonates: Facile Synthesis of Perfluoroalkylated Pyrazolo[1,5-a]pyridines Containing a Phosphonate Moiety - Huang, Qi; He, Dong; Han, Jing; Chen, Jie; He, Weimin; Deng, Hongmei; Shao, Min; Zhang, Hui; Cao, Weiguo (Synthesis, 2018)
1,3-Zwitterions generated from N-aminopyridines in the presence of base are trapped by perfluoroalkynylphosphonates to yield a variety of perfluoroalkylated pyrazolo[1,5-a]pyridine derivatives bearing a phosphonate group. The salient features of these [3+2] cycloadditions include operational simplicity, good tolerance of functional groups, and good to excellent yields at room temperature.
Keywords: N-aminopyridine; perfluoroalkynylphosphonate; pyrazolo[1,5-a]pyridine; [3+2] cycloaddition; synthetic methodology